CoNiP/Au Multisegment Magnetic Nanowires: Synthesis and Aminothiophenol (4-ATP) Functionalization - Ngoc, Do Quang; Nu, Hoang Thi; Thiem, Luu Van; Quynh, Luu Manh; Tu, Le Tuan (VNU Journal of Science: Mathematics - Physics; Vol 33 No 2DO - 10.25073/2588-1124/vnumap.4198, 2017)
Abstract: The magnetic properties in CoNiP/Au multisegments nanowire were investigated. All the samples were prepared by electrodeposition method with pH of 5.5 and room temperature. The electrochemical potential of CoNiP was determined by cycle voltammetary. The crystalline structure and morphology of the samples were characterized by X-ray diffraction (XRD), Scanning Electron Miroscopy (SEM) and High-resolution transmission electron microscopy (HRTEM), respectively. The hysteresis loops were measured at room temperature using vibrating sample magnetometry (VSM). The SEM and TEM image showed that the CoNiP/Au nanowires with diameters about 50 nm. The lattice spacing of the  CoNiP samples were 0.205 nm. The obtained results of VSM show that, the coercivity is 1006 Oe. The 4-Aminothiophenol (4-ATP) functionalized CoNiP/Au were combined by inverse emulsion method in order to apply to biomedicine.  The characteristic Surface Enhanced Raman peak positions of 4-ATP absorbed on the Au segments were occurred without any alterations, which significantly predicted attractive applicability of the colloids for biomedical labeling.